How do diffusion entrepreneurs spread policies ? : insights from performance-based financing in Sub-Saharan Africa - (:unkn) unknown (My University, 2018)
There has been growing interest in the diffusion of policy innovations across countries. Research on policy diffusion is characterised by coherent explanatory models that assess the importance of diffusion mechanisms. This study takes a different perspective on diffusion studies and advances public policy literature by introducing the concept of "diffusion entrepreneurs". These entrepreneurs represent (groups of) individuals, networks, and organisations promoting a certain policy innovation with a view to gain influence. First, drawing from the diffusion literature and linking it to studies investigating policy diffusion in polycentric contexts, we introduce analytical categories to study diffusion entrepreneurs' key features and actions. Second, to illustrate the analytical value of the concept, we conduct an in-depth analysis of the literature on the diffusion entrepreneurs of health performance-based financing (PBF) in Sub-Saharan Africa. We show how and why this recently diffused policy innovation provides a unique case for demonstrating our conceptual notion: in PBF, a nexus of strongly dedicated diffusion entrepreneurs have strived to induce policy diffusion. Specifically, we explore how the features of PBF diffusion entrepreneurs and their actions affect the outcomes of diffusion processes. Lastly, we reflect on the relevance of our conceptual propositions and offer practical insights to guide future investigations.
Keywords: African Research